The impact of IRT and IDT on metaverse adoption in tourism: The moderating role of personal innovativeness among China's generation Z. - Weifang Zhan; Yaru Shi; Chengpeng Lin (PLoS ONE, 2025)
This study examines the Metaverse-a virtual world that merges entertainment, work, and social interactions-in terms of leisure tourism, using the frameworks of innovation resistance and diffusion theories. It explores the factors that drive and hinder Chinese Gen Z tourists' resistance to Metaverse technology, including the moderating role of personal innovativeness. An analysis of data from 400 Chinese Gen Z tourists revealed that, in addition to risk barriers, factors such as value, usage, image, and traditional barriers significantly impact innovation resistance. Conversely, this resistance is mitigated by compatibility, trialability, and relative advantage, as outlined in the Innovation Diffusion Theory (IDT). Additionally, Innovation resistance significantly and negatively affects usage intentions, while personal innovativeness influences innovation barriers and diffusion within the Metaverse. This study not only fills gaps in existing studies but also provides valuable insights for providers and developers of Metaverse tourism services.